Empirical Educational Research in German-speaking Countries. Review and Perspectives - Maag Merki, Katharina (Swiss Journal of Educational Research, 2021)
The growth of empirical educational research in the German-speaking world over the past twenty years is related to the results of international large-scale assessments such as PISA and TIMSS, the implementation of new forms of governance, and the provision of extensive structural measures. This article first discusses “empirical educational research” as a field of research. In a second step, current research gaps are described. A need for research can be identified from a theoretical and methodological perspective and with regard to clarifying questions about the influencing factors and effects of educational processes. Furthermore, the development of a research infrastructure for educational research is advocated.